Взаимодействие атомарного водорода с поверхностью монокристаллов кремния - Zhavzharov, E. L.; Matushin, V. M. (PE "Politekhperiodika", Book and Journal Publishers, 2006)
The effect of atomic hydrogen on silicon single crystals was investigated at 300–310 K, with a chamber pressure of 20 Pa and an atomic hydrogen concentration of about 1019 m–1. Silicon samples of both conductivity types, including n-type Si with (100) and (111) orientations, were treated in an atomic hydrogen environment for 30–720 s. It was shown that exposure to atomic hydrogen leads to changes in the electrophysical parameters of silicon crystals and of metal–semiconductor structures fabricated on their basis. A physical mechanism explaining the observed results is proposed.